Centrifugation-induced fibrous orientation in fish-sourced collagen matrices. Issue 48 (4th December 2017) - Zhang, Juntao; Sun, Yang; Zhao, Yan; Wei, Benmei; Xu, Chengzhi; He, Lang; Oliveira, Cristiano L. P.; Wang, Haibo
Abstract : An aligned fibrous collagen matrix is fabricated at the macroscale by centrifugation. Abstract : Orientation of fibrous collagen structures plays an important role not only in the native function of various biological tissues but also in the development of next-generation tissue engineering scaffolds. However, the controlled assembly of collagen in vitro into an anisotropic structure, avoiding complex technical procedures and specialized apparatus, remains a challenge. Here, an oriented collagen matrix was fabricated at the macroscale by simple centrifugation, and the aligned topographical features of the resulting collagen matrix were revealed by scanning electron microscopy (SEM), transmission electron microscopy (TEM), and small angle X-ray scattering. The aligned matrix exhibited a higher ultimate tensile strength and strain than a random matrix. Centrifugation had an impact on the diameter and density of the collagen fibrils, while it had no effect on their native D -periodicity and thermal stability. Additionally, structural anisotropy of the collagen matrix facilitated the proliferation and migration of NIH/3T3 fibroblasts, compared with the random one. This simple and cost-effective method could lead to mass production of aligned collagen matrices and future possibilities for different applications in tissue engineering.